A study on the perception of LIS students and faculty of selected schools offering BLIS on their information technology courses - De Leon, Simon V. (2012)
Library and Information Science (LIS) as a field of study has grown over the years in order to better cope with new standards and practices. One of the examples of this growth is the inclusion of several changes to the Bachelor of Library and Information Science (BLIS) curriculum.